Saliva as a non-invasive tool for monitoring oxidative stress in swimmers athletes performing a VO2max cycle ergometer test - Biagini, Denise; Lomonaco, Tommaso; Ghimenti, Silvia; Fusi, Jonathan; Cerri, Eugenio; De Angelis, Francesca; Bellagambi, Francesca Giuseppa; Oger, Camille; Galano, Jean Marie; Bramanti, Emilia; Franzoni, Ferdinando; Fuoco, Roger; et al. (Talanta (Oxford), 2020)
Biomarkers of oxidative stress are generally measured in blood and its derivatives. However, the invasiveness of blood collection makes the monitoring of such chemicals during exercise not feasible. Saliva analysis is an interesting approach in sport medicine because the collection procedure is easy-to-use and does not require specially-trained personnel. These features guarantee the collection of multiple samples from the same subject in a short span of time, thus allowing the monitoring of the subject before, during and after physical tests, training or competitions. The aim of this work was to evaluate the possibility of following the changes in the concentration of some oxidative stress markers in saliva samples taken over time by athletes under exercise. To this purpose, ketones (i.e. acetone, 2-butanone and 2-pentanone), aldehydes (i.e. propanal, butanal, and hexanal), α,β-unsaturated aldehydes (i.e. acrolein and methacrolein) and di-carbonyls (i.e. glyoxal and methylglyoxal) were derivatized with 2,4-dinitrophenylhydrazine, and determined by ultra-high performance liquid chromatography coupled to diode array detector. Prostaglandin E2, F2/E2-isoprostanes, F2-dihomo-isoprostanes, F4-neuroprostanes, and F2-dihomo-isofuranes were also determined by a reliable analytical procedure that combines micro-extraction by packed sorbent and ultra-high performance liquid chromatography-electrospray ionization tandem mass spectrometry. Overall the validation process showed that the methods have limits of detection in the range of units of ppb for carbonyls and tens to hundreds of ppt for isoprostanes and prostanoids, very good quantitative recoveries (90–110%) and intra- and inter-day precision lower than 15%. The proof of applicability of the proposed analytical approach was investigated by monitoring the selected markers of oxidative stress in ten swimmers performing a VO2max cycle ergo meter test. The results highlighted a clear increase of salivary by-products of oxidative stress during exercise, whereas a sharp decrease, approaching baseline values, of these compounds was observed in the recovery phase. This study opens up a new approach in the evaluation of oxidative stress and its relation to aerobic activity. [Display omitted] •Analytical approaches to determine salivary markers related to oxidative stress.•Exercise enhanced the production of carbonyls, isoprostanes and prostanoids.•Saliva as a non-invasive diagnostic medium in sport medicine.